Perancangan Desain Komunikasi Visual Sebagai Identitas Brand dan Media Promosi Untuk Produk Bakeazy - Milviani, Christie; Saputra, Ellen (Jurnal VICIDI, 2020)
Premix box is a very popular thing nowadays. The sense of it being very practical yet efficient are some of the bases that make this instant product in high demand. The product that was developed by the writer is the byproduct of the innovated and elevated current premix boxes that are available on the market. The writer designs a strategy to put Bakeazy to the market; in a way that it would compete other premix boxes. Some of the strategies include adding certain ingredients to Bakeazy so that they are better both in taste and texture, compared to other competitors; and by doing numerous creative and unordinary promotions to attract publics’ attention to Bakeazy. By mentioning things above, the writer believes that Bakeazy would compete well with other competitors on the market. The writer did both quantitative and qualitative research by collecting data from consented participants. These data were collected by doing interviews, observations, and last but not least, literature studies. Based on the data results, participants showed positive responses towards Bakeazy.